Why skyscrapers after Covid-19?. (December 2021) - Smith, Richard G.
Highlights: Global cities and their skyscrapers will be more important after Covid-19 despite an increase in remote working. Skyscrapers outside of global cities, in both the Global North and South, will be less important after Covid-19. Skyscraper demand in global cities will strengthen to facilitate in-person interactions in specialised high-value fields. Global cities will drive GDP more than before, attracting wealth and demand for luxury residential skyscrapers. The location and usage of any skyscraper matters more than its height or reasons for construction. Abstract: Globalization's need for global cities with highly concentrated financial districts is discussed to explain how the Covid-19 pandemic will paradoxically only serve to make the world's leading global cities more essential, valuable, and demanding of skyscrapers than ever before. Financial and corporate service firms cannot only be digitally based because they also require face-to-face interaction, collaboration, and joint-production within themselves, and between one another, in the most connected global cities to effectively function as competitive businesses. However, after Covid-19 advanced service firms will only not practice remote working where and when they must; so that in-place face-to-face interactions with colleagues and clients will be overwhelmingly only concentrated in the skyscraper-laden financial districts of the world's leading global cities. The future of commercial and luxury residential skyscrapers in the world's leading global cities can be said to be secure because the impact of Covid-19 on enhancing the centrality of these few highly connected and super-wealthy cities in globalization is both understandable and predictable; skyscrapers elsewhere in the Global North or South will struggle to remain viable as firms increasingly decentralise the work of their staff away from city centre offices.